2016
DOI: 10.1017/s003329171500224x
|View full text |Cite
|
Sign up to set email alerts
|

A novel sibling-based design to quantify genetic and shared environmental effects: application to drug abuse, alcohol use disorder and criminal behavior

Abstract: Background Twin studies have been criticized for upwardly biased estimates that might contribute to the missing heritability problem. Method We identified, from the general Swedish population born 1960–1990, informative sibships containing a proband, one reared-together full- or half-sibling and a full-, step- or half-sibling with varying degrees of childhood cohabitation with the proband. Estimates of genetic, shared and individual specific environment for drug abuse (DA), alcohol use disorder (AUD) and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…These results provide no support for the hypothesis that twin studies overestimate the heritability of major depression. Our results are consistent with previous analyses using sibling designs that found that standard twin models do not overestimate the heritability of alcohol use disorder, drug abuse, or criminality (19). Inflated estimates from twin studies for the heritability of major depression are unlikely contributors to the "missing heritability problem.…”
Section: Estimation Of Heritability In Twin Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…These results provide no support for the hypothesis that twin studies overestimate the heritability of major depression. Our results are consistent with previous analyses using sibling designs that found that standard twin models do not overestimate the heritability of alcohol use disorder, drug abuse, or criminality (19). Inflated estimates from twin studies for the heritability of major depression are unlikely contributors to the "missing heritability problem.…”
Section: Estimation Of Heritability In Twin Studiessupporting
confidence: 90%
“…While SNP heritability might underestimate true heritability for many reasons, an additional explanation is that twin studies overestimate heritability (15)(16)(17)(18). With Scandinavian registries, it has become possible to compare heritability estimates from twin studies with those obtained from other genetically informative relationships that are not susceptible to the methodological problems of twin studies, although they have potential limitations of their own (19,20).…”
mentioning
confidence: 99%
“…However, a shared environment is significant only for the adolescent-limited ASB and explains only 30–40% of the variance (Eley et al 2003 ). Twin studies have been criticized for upwardly biased estimates that might contribute to the difference in estimated heritability between these two forms of ASB; therefore, a total population sibling-based or mixed design that uses both population-based sibling and twin designs has been proposed (Kendler et al 2015 , 2016 ). However, the explanatory effect derived from studies involving twins, adopted siblings and population siblings have important limitations in terms of G×E research because models of such designs often pre-suppose non-interaction effects and often lack the G×E term in their models (Plomin et al 1977 ).…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse and alcoholism are widely known to be running in families, and research shows both environmental and genetic causes (Thapar, 2015; Kendler et al, 2016). A meta-analysis in Sweden reviewing substance abuse and addiction among ADHD populations and their relatives, found a strong correlation among the two.…”
Section: Comorbidities In Various Presentations Of Adhdmentioning
confidence: 99%